Thermochemical study for remediation of highly concentrated acid spill: Computational modeling and experimental validation. (May 2020) - Jung, Hyunwook; Shin, Taesub; Cho, Namjun; Kim, Tae-kyung; Kim, Jongwoon; Ryu, Tae In; Song, Ki Bong; Hwang, Seung-Ryul; Ryu, Beyong-Hwan; Han, Byungchan
Abstract: The release of concentrated acid solutions by chemical accidents is disastrous to our environmental integrity. Alkaline agents applied to remedy the acid spill catastrophe may lead to secondary damages such as vaporization or spread out of the fumes unless substantial amount of neutralization heat is properly controlled. Using a rigorous thermodynamic formalism proposed by Pitzer to account short-range ion interactions and various subsidiary reactions, we develop a systematic computational model enabling quantitative prediction of reaction heat and the temperature change over neutralization of strongly concentrated acid solutions. We apply this model to four acid solutions (HCl, HNO 3, H 2 SO 4, and HF) of each 3 M-equivalent concentration with two neutralizing agents of calcium hydroxide ( Ca ( OH ) 2 ) and sodium bicarbonate ( NaHCO 3 ). Predicted reaction heat and temperature are remarkably consistent with the outcomes measured by our own experiments, showing a linear correlation factor R 2 greater than 0.98. We apply the model to extremely concentrated acid solutions as high as 50 wt% where an experimental approach is practically restricted. In contrast to the extremely exothermic Ca ( OH ) 2 agent, NaHCO 3 even lowers solution temperatures after neutralization reactions. Our model enables us to identify a promising neutralizer NaHCO 3 for effectively controlling concentrated acid spills and may be useful for establishment of proper strategy for other chemical accidents. Graphical abstract: Image 1 Highlights: Computational framework for understanding thermochemistry in acid spill remediation. Accurate prediction and validation of reaction heat and temperature change. Rigorous description of short-range ionic interaction through Pitzer formalism. Discovery of superior alternative to conventional agent and working mechanisms.